2007
DOI: 10.1103/physrevb.75.054419
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the crystalline structure, morphology, and magnetic properties ofγ-phaseMnCu3Au(100)ultrathin films by varying

Abstract: The structural and magnetic properties of room-temperature ͑RT: 300 K͒-grown and low-temperature ͑LT: 100 K͒-grown Mn/ Cu 3 Au͑100͒ thin films were investigated. Mn films deposited at RT and LT demonstrate very different behaviors in the crystalline structure, morphology, and magnetism. RT-Mn films reveal apparent layer-by-layer growth for 0 -2 ML ͑monolayer͒ followed by reduced oscillations. Although the medium-energy electron diffraction ͑MEED͒ oscillation is reduced, the intensity of specular spot increases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 45 publications
5
11
0
Order By: Relevance
“…The regular oscillation indicates a well-defined layer-by-layer growth mode, in which the flat surface with around two monoatomic steps has been observed by STM. 27,29 As t Mn > 11 ML, the oscillation was found to vanish coincidentally with the fcc-fct structural transition as reported in the previous studies. 27,30 Experimentally, there are four different phases observed for the bulk Mn.…”
Section: Methodssupporting
confidence: 85%
See 3 more Smart Citations
“…The regular oscillation indicates a well-defined layer-by-layer growth mode, in which the flat surface with around two monoatomic steps has been observed by STM. 27,29 As t Mn > 11 ML, the oscillation was found to vanish coincidentally with the fcc-fct structural transition as reported in the previous studies. 27,30 Experimentally, there are four different phases observed for the bulk Mn.…”
Section: Methodssupporting
confidence: 85%
“…27,29 As t Mn > 11 ML, the oscillation was found to vanish coincidentally with the fcc-fct structural transition as reported in the previous studies. 27,30 Experimentally, there are four different phases observed for the bulk Mn. The α phase has a complex cubic structure with 58 atoms per unit cell and noncollinear AFM order which disappears above the Néel temperature of 95 K. 31 For the temperature above 1073 K, a transition to a cubic structure with 20 atoms per unit cell occurs, namely the β phase.…”
Section: Methodssupporting
confidence: 85%
See 2 more Smart Citations
“…Among various antiferromagnets, face-centered-cubic (fcc)-like Mn thin films are considered to be highly attractive systems because they can be fabricated with current epitaxial growth techniques [19][20][21][22][23][24][25][26]. Although theoretical studies have suggested that the behavior of bulk fcc-like Mn could be a function of the lattice parameters, on the basis of the rich magnetic phase diagram of bulk fcc-like Mn [27,28], for Mn thin films directly grown on FM films with stable in-plane magnetization (or vice versa), experiments involving spinpolarized scanning tunneling microscopy (SP-STM) and x-ray magnetic circular dichroism (XMCD)-based photoemission microscopy (PEEM) have supported in-plane layered AFM structures [10,23,24,29].…”
Section: Introductionmentioning
confidence: 99%